Facultative polypeptide translocation allows a single mRNA to encode the secreted and cytosolic forms of plasminogen activators inhibitor 2. - Belin, D (1989)
Two forms of plasminogen activators inhibitor 2 (PAI-2) are synthesized by human and murine monocytes/macrophages: one accumulates in the cytosol, while the other is translocated into the endoplasmic reticulum, glycosylated and secreted. We show here that a single mRNA encodes both forms of PAI-2. Firstly, a single PIA-2 mRNA was detected by Northern blot hybridization and by RNase protection. Secondly, transfection of a PAI-2 cDNA led to the synthesis of both forms of PAI-2. Finally, in vitro translation of an mRNA transcript of the PAI-2 cDNA in the presence of microsomal membranes generated two topologically distinct forms of PAI-2. The cytosolic and secreted forms of PAI-2 do not result from the use of two translation start sites, since their synthesis initiates at the same AUG, in a sequence context that is conserved between the human and murine genes. Thus, the accumulation of one polypeptide into two topologically distinct cellular compartments can be achieved by facultative translocation.